La naturaleza como casa encantada: la ecología al servicio del terror en Mariana Enriquez y Luciano Lamberti - Ferrari, Enrique (2024)
Mariana Enriquez and Luciano Lamberti take advantage of the widespread ecological sensitivity of our time to provide new disruptive devices to introduce supernatural terror into their stories. They transform the haunted house into natural spaces, which maintain the same characteristics and reactions as the former, but are more in tune with the reader’s concerns. A nature that is hostile because it has been previously mistreated (such as a polluted stream or an abandoned and dirty forest), functions as a haunted house and as a monster. It is a symbolic expression of the taboo upon which an economic development that has ignored so many victims has settled.